Major depressive episode in hospital workers during the Covid-19 pandemic in Brazil - Flesch, Betina Daniele; Szortyka, Ana Laura Sica Cruzeiro; Carvalho, Maitê Peres de; Goularte, Laura Moreira; Delpino, Felipe Mendes; Fassa, Anaclaudia Gastal (Revista de Saúde Pública, 2022)
OBJECTIVES: To estimate prevalence and factors associated with major depressive episode (MDE), emphasizing occupational aspects, in workers of a public teaching hospital that is a reference for Covid-19 treatment. METHODS: A cross-sectional study was carried out between October and December 2020, after the first peak of the pandemic, interviewing 1155 workers. The prevalence of MDE was estimated using the Patient Health Questionnaire (PHQ-9) algorithm. Multivariate hierarchical analysis was conducted using Poisson regression to assess associated factors. RESULTS: MDE prevalence was 15.3% (95%CI: 13.3–17.5) and was higher among young, white and female workers, those with a family history of depression, resident professionals, nursing professionals, workers who were exposed to three or more situations of moral dilemma, and those who had to put off a physiological need until later. Having a risk factor for Covid-19, being a smoker and being physically inactive were also positively associated with MDE. CONCLUSIONS: The study points to the considerable prevalence of MDE among tertiary health care workers; reviewing work processes is essential to reduce occupational stress and minimize the effects of the pandemic on mental health, preventing those problems from becoming chronic.